(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
In this interview, Scott Hall—Director of Workforce Development at Eastern Shore Community College (ESCC) in rural Virginia—describes how a small community college is building practical “pathways for learners” that connect adult education, workforce credentials, and academic programs for immigrant and multilingual students. Hall explains how Virginia’s FastForward credentialing model, WIOA-funded services, and integrated education and training (IET) courses create low-cost, high-impact routes into fields like CDL and healthcare, while also addressing real barriers such as transportation, food insecurity, and shifting federal and state policy constraints. A central focus is ESCC’s emerging approach to recognizing learners’ prior education and experience—especially through transcript translation/evaluation, clear English-skills milestones using CASAS, and flexible committee review when standardized cut scores create unnecessary obstacles.